On the genus Thalerommata Ausserer, 1875 (Araneae, Theraphosidae), with the description of six new species - Bertani, Rogerio; Raven, Robert J. (Zootaxa, 2023)
The poorly known mygalomorph genus Thalerommata Ausserer, 1875 is redescribed and rediagnosed. Thalerommata gracilis Ausserer, 1875 (type species) and T. macella (Simon, 1903) are rediagnosed. Thalerommata meridana (Chamberlin & Ivie, 1938) is considered a nomen dubium. Six new species are described: T. squamea n. sp., T. huila n. sp., T. splendens n. sp., T. pecki n. sp., T. maculata n. sp., and T. gertschi n. sp. Thalerommata is transferred from Barychelidae to Theraphosidae and considered closely related with Trichopelma Simon, 1888, with which it shares the biserially dentate superior tarsal claws in males in combination with non-incrassate PLS. The genus is distributed from northern South-America to the Caribbean.